Benefits of aromatase blockers for increased testosterone in poultry: A mini-review - Rizki Fitrawan Yuneldi; Claude Mona Airin; Sarmin Sarmin; Andhika Yudha Prawira; Pudji Astuti (Veterinary World)
Background and Aim: Testosterone is a key androgenic hormone in male poultry, regulating growth performance, reproductive function, and the development of secondary sexual characteristics. However, endogenous testosterone levels are often diminished through conversion to estrogen through the aromatase enzyme, presenting a physiological constraint in poultry production systems. While synthetic testosterone administration has been employed to overcome this limitation, it is frequently accompanied by adverse effects, including gonadal atrophy and impaired spermatogenesis. Consequently, aromatase blockers have emerged as a promising strategy to enhance testosterone levels by inhibiting estrogen biosynthesis. This review synthesizes current evidence on both synthetic aromatase blockers (SABs), such as letrozole and tamoxifen, and natural aromatase blockers (NAB), including compounds derived from Anadara granosa and Anadara nodifera clamshells, plant extracts, and trace minerals like zinc. The mechanisms, efficacy, physiological effects, and safety profiles of NAB are comparatively examined against SAB. The findings indicate that NAB can significantly elevate testosterone levels and improve reproductive and performance traits without the adverse histopathological effects observed with prolonged SAB or synthetic androgen use. This review highlights the potential of NAB as sustainable alternatives to synthetic hormones in poultry production and recommends further investigations to optimize dosing regimens, elucidate long-term effects, and explore combinatorial strategies.